Effect of Arm Eccentric Exercise on Muscle Damage of the Knee Flexors After High-Intensity Eccentric Exercise - Ye, Xin; Miller, William M.; Jeon, Sunggun; Song, Jun Seob; West, Tyler J. (Frontiers in Physiology, 2021)
Repeated bout effect (RBE) describes a phenomenon that an initial unaccustomed eccentric exercise (ECC) bout can confer a protective effect against muscle damage from the subsequent same exercise. This protection has been observed in the same muscle, as well as the contralateral homologous (CL-RBE) muscle. But it is unknown whether the RBE is evident for non-local unrelated heterogonous muscles. The purpose of this study was to examine whether an initial elbow flexion (EF) muscle-damaging ECC could confer RBE against muscle damage from the subsequent ECC performed in the remote lower limb knee flexor (KF) muscle group. Twenty-seven young individuals were randomly assigned into the experimental (EXP: n = 15) and the control (CON: n = 12) groups. All participants performed a baseline unilateral KF ECC (6 sets of 10 repetitions) on a randomly chosen leg. After a washout period (4 weeks), the EXP group performed 60 high-intensity unilateral EF ECC on a randomly chosen arm, followed by the same intensity exercise using the contralateral KF muscle group 2 weeks later. The CON group performed the same contralateral KF ECC, but with no prior EF ECC bout. Changes in the KF muscle damage indirect markers (muscle soreness, range of motion, maximal isometric strength) after the ECC were compared between the baseline and second bouts for both groups with mixed factorial three-way (group × bout × time) analyses of variance (ANOVA). Additionally, the index of protection for each damage marker was calculated at 1 day and 2 days after the ECC and compared between groups with independent t-tests. For both groups, the magnitude of the changes in the damage markers between the baseline and the second ECC bouts were not significantly different (all p-values > 0.05). As for the index of protection, relative to the CON, the EXP showed an exacerbating damaging effect on the KF isometric strength following the second ECC bout, particularly at the 1-day post-exercise time point (index of protection: EXP vs. CON mean ± SD = -29.36 ± 29.21% vs. 55.28 ± 23.83%, p = 0.040). Therefore, our results do not support the existence of non-local RBE.